HUBUNGAN MATA KULIAH MICRO TEACHING TERHADAP KETERAMPILAN MENGAJAR MAHASISWA - Anisya Dita Einsthendi (EDUTECH, 2023)
Abstract: Micro teaching serves as an initial stage in shaping teaching competence for aspiring educators, with its main focus being the refinement of teaching skills through an approach based on each indicator of teaching skills. This research addressed the role of Micro Teaching in developing teaching skills for prospective teachers.  Micro teaching is expected to address deficiencies in the Education program and aid prospective educators in comprehensively mastering the components of teaching skills. However, this study indicated that teaching skills are not solely determined by Micro Teaching, but are more dominantly influenced by teaching experience and direct teaching practice. That study involved students from various disciplines, with 100 respondents selected using purposive sampling techniques. The research findings reveal that there is no significant correlation between the Micro Teaching course and teaching skills. These results suggest that Micro teaching is not the sole determinant. This study is also consistent with other findings that emphasize the significant impact of Education, Training, and teaching experience on the enhancement of teaching skills.Keyword:Micro Teaching, Teaching Skills, Teaching Practice